PENGARUH MUSIK TERHADAP KEMAMPUAN MATEMATIK MAHASISWA TEKNIK INDUSTRI UNIVERSITAS SEBELAS MARET - Sari, Riska Permana; Adiworo, Praditya; Suhardi, Bambang (Performa: Media Ilmiah Teknik Industri, 2017)
The aim this research is; 1) to know the influence of music on the ability of mathematics student; 2 ) to know the type of music is more significant impact on the ability of mathematics. A kind of experiment the design chosen is the design of experiment single-factor experiment. Respondents in this research is a student of industrial engineering university of surakarta eleven march 2013. The experiments in this research are 20 students with twice replication the answer given by the writers math problem. Variable ability mathematics is measured in terms of the answer. During the experiment four of kind music compare with without music. The result of this peper Music increase math ability of student.